CREDIBILITY GUARANTEEING OF METERS READOUTS - Shamanskyi, Sergii (Proceedings of National Aviation University (archive), 2015)
The article deals with a credibility problem of resource amounts calculation. The calculation is based on periodical readouts of meters registrations. We propose a model of readout errors calculation and an estimation model of time lags between the readouts to provide errors in a necessary range.